Ground Attack Strategy of Cooperative UAVs for Multitargets - Qirui Zhang; Ruixuan Wei (Complexity)
Humans have a fundamental ability, that is, to share vision among each other to fulfill common goals, which cooperative UAVs do not have. The difficulties mainly lie in the homologous mathematical description of humans and elusive experimental practice. This paper proposed a parallel multiview splicing on clouds, which first review both theory and practice studies in UAVs. These terms are then reconsidered from humans’ vision sharing. Next, a conceptual model of parallel multiview splicing on clouds is proposed and the mathematical deduction if fulfilled. Furthermore, an experimental cooperative UAVs platform is built to practically implement the algorithms. Both the simulated and practiced results have validated the feasibility of our method. Finally, a general discussion and proposals for addressing future issues are given.